PERBEDAAN PRESTASI BELAJAR SISWA MATA PELAJARAN IPS DENGAN M0DEL PEMBELAJARAN JIGSAW DAN MODEL PEMBELAJARAN STAD - Munawaroh, (Pendidikan Dasar, 2010)
Abstract: This research aims at comparing the achievement in social science between students taught using Jigsaw and those using STAD. The sample consists of 66 students taken from VIII A and VIII B of SMP 5 Jombang. After analysing the data  using t- test, it is found out that the class taught using Jigsaw achieves better than the one taught using STAD.